2008
DOI: 10.1128/aac.00793-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of a Highly Effective Fusion Inhibitor for Human Metapneumovirus

Abstract: Human metapneumovirus (hMPV) can cause acute upper and lower respiratory tract infections that are particularly severe in young children, elderly subjects, and immunocompromised patients. To date, no treatments or vaccines are available for hMPV infections. Our objective was to assess the inhibitory potential of several peptides derived from the heptad repeat A and B (HRA and HRB) domains of the hMPV fusion protein. Nine candidate peptides were expressed in Escherichia coli or obtained synthetically and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 47 publications
(57 reference statements)
1
49
0
Order By: Relevance
“…At the same time, the pulmonary levels of IFN-␥ and MCP-1 were significantly greater in the young mice than in the aged mice. These results are in accordance with those of Deffranes et al (12), who reported a lesser degree of airway obstruction concomitant with lower levels of IFN-␥, MCP-1, and RANTES in mice treated with a peptide derived from the hMPV fusion protein (12). Two studies on RSV infection with high inoculum titers described a significant increase in AO associated with a high IFN-␥ concentration and cellular infiltration of the lungs (28,54).…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, the pulmonary levels of IFN-␥ and MCP-1 were significantly greater in the young mice than in the aged mice. These results are in accordance with those of Deffranes et al (12), who reported a lesser degree of airway obstruction concomitant with lower levels of IFN-␥, MCP-1, and RANTES in mice treated with a peptide derived from the hMPV fusion protein (12). Two studies on RSV infection with high inoculum titers described a significant increase in AO associated with a high IFN-␥ concentration and cellular infiltration of the lungs (28,54).…”
Section: Discussionsupporting
confidence: 81%
“…Potential treatment strategies include ribavirin, immunoglobulin administration (46), and fusion inhibitors (47). Virus-specific MAb are currently available for the prevention of RSV in high-risk infants and such preventive therapy may be available for hMPV in the future.…”
Section: Human Metapneumovirusmentioning
confidence: 99%
“…[26][27][28][29] The ineffectiveness of the natural infection to induce long-term immunity has hampered vaccine generation and currently there is no licensed vaccine available to prevent the bronchiolitis and pneumonia caused either by hRSV or hMPV. [30][31][32][33][34] However, several candidate vaccines are in different stages of development for preventing the diseases caused by these viral agents. Candidate vaccines for hRSV and hMPV employ different approaches, including a chimeric virus (hMPV), 35 live attenuated virus (hRSV), 36 and purified proteins (hRSV), 37 among others.…”
Section: Introductionmentioning
confidence: 99%